Implementasi Sistem Informasi Pendidik dan Tenaga Kependidikan (SIMPATIKA) Seksi Pendidikan Madrasah di Kantor Kementerian Agama Kota Palangka Raya (International Forum of Researchers and Lecturers, 2024)
This article aims to describe the implementation of the Madrasah Education Section's Educator and Education Personnel Management Information System (SIMPATIKA) at the Palangka Raya City Office of the Ministry of Religious Affairs. The main focus in this research includes: implementation, effectiveness of use, and inhibiting factors of SIMPATIKA implementation. This research was conducted qualitatively with data collection through in-depth interviews, observation, and documentation. The results showed that: 1) The implementation of SIMPATIKA has been carried out by the Madrasah Education Section at the Palangka Raya City Ministry of Religious Affairs Office, which is managed by SIMPATIKA Special operators.2) The effectiveness of using SIMPATIKA as a madrasah data management system has not been fully realized.3) The inhibiting factors of SIMPATIKA implementation are mainly caused by the ignorance of some teachers in accessing the management information system for educators and education personnel (PTK). This has led to the delegation of SIMPATIKA account management to madrasah operators, whereas the account should be managed individually by each educator. The proposed solution is to hold technical guidance on the SIMPATIKA management information system, and provide an understanding of the rights and responsibilities in using individual SIMPATIKA accounts..